2015
DOI: 10.1007/s10661-015-4744-7
|View full text |Cite
|
Sign up to set email alerts
|

Produced water irrigation changes the soil mesofauna community in a semiarid agroecosystem

Abstract: The scarcity of water in semiarid regions requires alternative sources for irrigation to improve agricultural production. Here, we aimed to evaluate the effects of produced water from oil exploration on the structure of soil mesofauna during the dry and rainy seasons in irrigated sunflower and castor bean fields in a Brazilian semiarid region. Three irrigation treatments were applied on plots cultivated with castor beans and sunflowers: produced water treated by filtration (filtrated) or treated by reverse osm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…From Tables 1 and 2 it can be seen that in general the Bact populations was higher in the second crop cycle, coinciding with with rainy periods in the region (FERREIRA; WEBER; CRISÓSTOMO, 2015), and during vegetative growth, as a result of the ground cover. Lopes et al (2014), studying the effect of produced water on soil microbial activity, found a higher population density for cultivable bacteria at the flowering stage of the first cycle of the sunflower cv.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…From Tables 1 and 2 it can be seen that in general the Bact populations was higher in the second crop cycle, coinciding with with rainy periods in the region (FERREIRA; WEBER; CRISÓSTOMO, 2015), and during vegetative growth, as a result of the ground cover. Lopes et al (2014), studying the effect of produced water on soil microbial activity, found a higher population density for cultivable bacteria at the flowering stage of the first cycle of the sunflower cv.…”
Section: Resultsmentioning
confidence: 91%
“…There was little change in the organic fertiliser from soil moisture (<5%) under rainfed conditions due to the low rainfall intensity in the area (FERREIRA; WEBER; CRISÓSTOMO, 2015). It is worth noting that oilseed production was only seen during the second cycle (April to July 2013), when a total of 448 mm of rain was registered.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Eid et al, (2014) published that recycling the drainage water of fish farming, rich with organic matter for agriculture use can improve soil quality and crops productivity and reduce the total costs of fertilizers by adding minimum doses from minerals fertilizers. Ferreira et al, (2015) found that irrigation with produced water promotes important changes in soil fauna structure that justify its assessment for the maintenance and monitoring of agro-ecosystems. To our knowledge, this is the first evidence of how the mesofauna structure is influenced by the quality of water used for irrigation.…”
Section: Iii-dominance and Abundance Degrees Ofmentioning
confidence: 99%
“…However, produced water should not be applied at excessive rates to the soil surface or reused without treatment, because it may present high contents of disperse oil, total dissolved solids, inorganic chemical compounds, and heavy metals (Al-Ghouti et al, 2019), requiring previous evaluations for accumulations of potentially toxic elements in the soil and plant tissues (Ferreira et al, 2015;Pica et al, 2017;Echchelh et al, 2019).…”
Section: Introductionmentioning
confidence: 99%